The role of diffusion of innovation theory towards the adoption of halal meat supply chain - Ghulam Qader; Zubair Ali Shahid; Muhammad Junaid; Imran Mehboob Shaikh; Muhamamd Asif Qureshi (Emerald Group Publishing Limited, 2022)
This paper aims to examine the factors that drive the exporter’s influence toward halal meat supply chain adoption by encompassing the diffusion of innovation (DOI) theory in the context of Pakistan. Using DOI as an underpinning theory, this study evaluates halal supply chain adoption by collecting data from the members of associations from Pakistan. A total of 258 useable responses were received, and PLS-SEMwas adopted using SmartPLS. The exporter’s adoption of the halal supply chain is determined not only by perceived relative advantage and perceived compatibility but also by perceived complexity, religious beliefs and awareness. Though this study has practical and managerial implications, it has few limitations. Further studies need to be conducted in other contexts as well with a larger population. There are limited studies that have tested DOI theory in the context of the halal meat supply chain in Pakistan. Therefore, the author extends the diffusion theory of innovation in the current work. Further, this paper will be a helpful reference guide for academicians, practitioners and researchers.